2021
DOI: 10.1097/fjc.0000000000001104
|View full text |Cite
|
Sign up to set email alerts
|

Circ-USP9X Inhibition Reduces Oxidized Low-density Lipoprotein–induced Endothelial Cell Injury via the microRNA 599/Chloride Intracellular Channel 4 Axis

Abstract: Atherosclerosis (AS) is the common pathological basis of cardiovascular disease. Circular RNA circ-USP9X (hsa_-circ_0090231) has been discovered to be upregulated in oxidized low-density lipoprotein (ox-LDL)-induced human umbilical vein endothelial cells (HUVECs), but the role of circ-USP9X in ox-LDLinduced endothelial cell injury is indistinct. The purpose of the research was to investigate the role and regulatory mechanism of circ-USP9X in ox-LDL--induced endothelial cell injury. Expression of circ-USP9X was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Circ_0090231 has been reported to function as a ceRNA that can regulate various biological processes by sponging miRNAs [ 26 ]. We employed Starbase 3.0 ( http://starbase.sysu.edu.cn/ ) to predict potential target miRNAs of circ_0090231.…”
Section: Resultsmentioning
confidence: 99%
“…Circ_0090231 has been reported to function as a ceRNA that can regulate various biological processes by sponging miRNAs [ 26 ]. We employed Starbase 3.0 ( http://starbase.sysu.edu.cn/ ) to predict potential target miRNAs of circ_0090231.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, USP9X has been implicated in several neurodevelopmental and neurodegenerative disorders and malignancies. CircRNA hsa_circ_0090231 (circ- USP9X ) is derived from the USP9X gene, which was elevated in ox-LDL–treated endothelial cells and promoted endothelial cell injury via the miR-599/CLIC4 axis ( 20 ). However, the role of USP9X protein in foam cell formation and atherogenesis has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are a new class of endogenous non-coding RNAs (ncRNAs) that do not have 5' caps and 3′ poly(A) tails and exist in their characteristic covalent closed-loop form. A growing number of studies have shown that circRNAs are widely present In Vivo, stably expressed in plasma, serum, and tissues, and involved in the regulation of eukaryotic gene expression [10,11]. circRNA-0024103 is a newly identified circRNA that has been studied to regulate MMP-10 expression in human cartilage degradation by acting as a miR-363 "sponge," but its function in cardiovascular disease is not yet clear.…”
Section: Introductionmentioning
confidence: 99%